2008
DOI: 10.4049/jimmunol.181.10.7176
|View full text |Cite
|
Sign up to set email alerts
|

TLR/MyD88 and Liver X Receptor α Signaling Pathways Reciprocally Control Chlamydia pneumoniae-Induced Acceleration of Atherosclerosis

Abstract: Experimental and clinical studies link Chlamydia pneumoniae infection to atherogenesis and atherothrombotic events, but the underlying mechanisms are unclear. We tested the hypothesis that C. pneumoniae-induced acceleration of atherosclerosis in apolipoprotein E (ApoE)−/− mice is reciprocally modulated by activation of TLR-mediated innate immune and liver X receptor α (LXRα) signaling pathways. We infected ApoE−/− mice and ApoE−/− mice that also lacked TLR2, TLR4, MyD88, or LXRα intranasally with C. pneumoniae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
126
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(136 citation statements)
references
References 56 publications
10
126
0
Order By: Relevance
“…It is known that pathogens such as C. pneumoniae can induce macrophage foam cell formation (28), an effect that might be increased if an individual has been infected by multiple pathogens (5). TLR/ MyD88 and liver X receptor signaling pathways reciprocally control C. pneumoniae-induced acceleration of atherosclerosis (29). It has been hypothesized that the infectious pathogen contains proteins that are homologous to parts of the host proteins, resulting in an immune response called infection-induced molecular mimicry (30).…”
Section: Pneumonia Infection and Atherogenesismentioning
confidence: 99%
“…It is known that pathogens such as C. pneumoniae can induce macrophage foam cell formation (28), an effect that might be increased if an individual has been infected by multiple pathogens (5). TLR/ MyD88 and liver X receptor signaling pathways reciprocally control C. pneumoniae-induced acceleration of atherosclerosis (29). It has been hypothesized that the infectious pathogen contains proteins that are homologous to parts of the host proteins, resulting in an immune response called infection-induced molecular mimicry (30).…”
Section: Pneumonia Infection and Atherogenesismentioning
confidence: 99%
“…The C57BL/6 wild-type and TLR2 knockout (KO) mice were purchased from Jackson Laboratories (Bar Harbor, ME), whereas TLR4 KO mice were kindly provided by Dr. Shizuo Akira (Osaka University, Osaka, Japan). A homogenous population of these mice was established by backcrossing onto the C57BL/6 background for at least 10 generations, as previously described (5). Mice were fed a standard chow diet and housed under specific pathogen-free conditions at Cedars-Sinai Medical Center.…”
Section: Micementioning
confidence: 99%
“…Chlamydophila pneumoniae is an obligate intracellular bacterium that can also exacerbate atherosclerosis and asthma (5,6). We showed that C. pneumoniae, depending on the infective dose, can lead to either a Th1 response, or can act as an adjuvant to induce allergic sensitization and lead to Th2-like immune responses in mice (6).…”
mentioning
confidence: 99%
“…For example, C. pneumoniae has been isolated from coronary arteries in patients with acute coronary syndrome (Saikku et al, 1988), and in experimental studies, it has been found that infection with C. Pneumoniae increases atherosclerotic plaque size in Apo E −/− mice compared to the controls. It has also been reported that the size of the aortic lesion and the expression of pro-inflammatory cytokines, such as MCP-1, IL-12p40, TNF-, and IL-6, are reduced in ApoE −/− TLR2 −/− , ApoE −/− TLR4 −/− and ApoE −/− MyD88 −/− mice when compared with the ApoE −/− controls infected with C. Pneumoniae (Naiki et al, 2008). Other studies have reported that HSP60 of C. Pneumoniae (cHSP60) reduces the expression and activity of nitric oxide synthase in the endothelial cells of the human coronary artery, which has also been associated with endothelial dysfunction.…”
Section: The Role Of Tlrs In Response To Infectious Agents In Atherosmentioning
confidence: 99%